Numerical investigation and performance evaluation of the MnFe-based composite magnetocaloric material with large magnetic entropy change over a wide temperature range. (January 2021) - Li, Yan; Lin, Guoxing; Chen, Jincan
Highlights: An Ericsson refrigeration cycle with MnFe-based composite materials is proposed. Molar mass ratios of each constituent to composite are optimally determined. Effects of non-perfect regeneration and applied magnetic field are discussed. The cooling quantity and coefficient of performance of the cycle are calculated. Cyclic performances with composite and each constituent materials are compared. Abstract: From the experimental data of the isofield heat capacity of the MnFe-based magnetocaloric materials, magnetic entropy change versus temperature characteristic curves are obtained by using numerical value calculation procedure. Three kinds of MnFe-based magnetocaloric materials, in which there are all a large magnetocaloric effect, are selected as the constituent materials to establish a novel composite magnetocaloric material, for which keeping large magnetic entropy change over a wide temperature range is desired. By means of thermodynamic analysis and optimal control theory, the molar mass ratios of each constituent material to the composite material are optimally determined for differently applied magnetic fields. The optimum results show that when the applied magnetic field μ 0 H″ =2 T, the optimum molar mass ratios x1opt, x2opt, and x3opt of Mn1.24 Fe0.76 P0.75 Ge0.25, Mn1.2 Fe0.8 P0.75 Ge0.25, and Mn1.1 Fe0.9 P0.78 Ge0.22 to the composite are equal to 0.44, 0.11, and 0.45, respectively. Furthermore, the regenerative Ericsson refrigeration cycle employing the composite or constituent materials as the working substance is set up. The effects of the non-perfect regeneration on the net cooling quantity, COP, etc. of the refrigeration cycle are analyzed and evaluated. The cycle performances of the composite material are compared with those of the constituent materials. It shows that the net cooling quantity and COP of the composite are much larger than those of any constituent material. The numerical calculation results obtained can provide some reference for the selection of working substances and the optimal parameter design of room temperature magnetic refrigerators.